A concurrent irradiation-mechanics multiscale coupling model. (October 2022) - Ji, Changqiu; Cui, Yinan; Li, Yang; Ghoniem, Nasr
Highlights: A novel concurrent irradiation-mechanical multiscale coupling model is developed. Models of irradiation defect kinetics and irradiation hardening are established. The difference between post irradiation and concurrent irradiation-deformation tests are disclosed. Dislocation channel formation is not always correlated with yield drop. Abstract: The vast majority of our current knowledge regarding the basic mechanisms controlling irradiation effect on mechanical properties is based almost entirely on the results of post-irradiation experiments or theoretical models. However, the concurrent effects of irradiation, mechanical stress, and thermal damage on the failure phenomena of materials and components remain largely unexplored due to its internal multiscale-multiphysics coupling nature. We present here a concurrent irradiation-mechanics multiscale coupling model. The concurrent evolutions of nanoscale irradiation defect clusters, microscale dislocation configurations, and mechanical responses are well captured based on coupling cluster dynamics, discrete dislocation dynamics, and the finite element methods using an effective time marching scheme. Model predictions of defect densities and size are in general agreement with experimental observations. Irradiation hardening is shown to take place also in samples undergoing concurrent irradiation-mechanical loading, similar to samples tested post-irradiation. However, the occurrence of plastic flow localization and dislocation channel formation is not accompanied with apparent yield drop (softening) under concurrent irradiation-mechanical loading conditions, which is different from the post-irradiation case.